Selenium intake and multiple health-related outcomes: an umbrella review of meta-analyses - Wang, Puze; Chen, Bo; Huang, Yin; Li, Jin; Cao, Dehong; Chen, Zeyu; Li, Jinze; Ran, Biao; Yang, Jiahao; Wang, Ruyi; Wei, Qiang; Dong, Qiang; et al. (Frontiers in Nutrition, 2023)
Selenium is an essential trace metalloid element that is associated with fundamental importance to human health. Our umbrella review aimed to evaluate the quality of evidence, validity, and biases in the relationship between selenium intake and health-related outcomes according to published systematic reviews with pooled data and meta-analyses. Selenium intake is associated with a decreased risk of digestive system cancers, all-cause mortality, depression, and Keshan disease, when in children reduce the risk of Kashin-Beck disease. Additionally, selenium supplementation can improve sperm quality, polycystic ovary syndrome, autoimmune thyroid disease, cardiovascular disease, and infective outcomes. Selenium supplementation also has relationship with a decreased concentration of serum lipids including total cholesterol and very low-density lipoprotein cholesterol. However, no evidence has shown that selenium is associated with better outcomes among patients in intensive care units. Furthermore, selenium intake may be related with a higher risk of type 2 diabetes and non-melanoma skin cancers. Moreover, most of included studies are evaluated as low quality according to our evidence assessment. Based on our study findings and the limited advantages of selenium intake, it is not recommended to receive extra supplementary selenium for general populations, and selenium supplementation should not be continued in patients whose selenium-deficient status has been corrected.